Sekolah Total Quality Management dalam Sebuah Manajemen Pendidikan Formal ISO 9001:2015 - Saajiz, Muhamad; Hafiza (Journal of Information Systems and Management (JISMA), 2024)
Education is one of the goals of life of the community both from the past until now. Education itself in its implementation really needs quality that guarantees that those who do it can be guaranteed quality and knowledge. Quality management is one of the things that underlies the quality of education. How this quality management will improve quality, equality, needs and what is needed for the smooth running of education and of course education that should be enjoyed by the community. And this quality management will affect the quality of a school itself.